Performance of Embeded of Precast Beam Type Wet and Dry Joint at Maximum Moment - A. Rudi Hermawan; Eka Sasmita Mulya (Applied Research on Civil Engineering and Environment (ARCEE), 2020)
Research of perform of embedded precast beam was result many data (a) average tensile strength of joint between plate embedeed with plate joint was 628,55 Mpa (b)average tensile strength of joint between plate with reinforce bar D12,59 was 597,16 Mpa for tensile strength of plate with failure at reinforce bar (c) average tensile strength of reinforce bar D12,59 was 605,23 Mpa and yield strength was 425,87 Mpa (d)average tensile strength of plate 4,58 mm thick was 456,86 Mpa and  yield strength was 335,02 Mpa. For welded joint need several control quality so that no hole in that perform of welded couse can decrease tensile strength of joint. Conclusion of this research is embedded for precast concrete type wet and dry can be used for construction of joints of beam.